Anthracnose risk establishment based on age-related susceptibility of grape leaves, flowers and berries to infection by Elsinoë ampelina - Carisse, Odile; Levasseur, Audrey; Provost, Caroline (Plant disease, 2021)
Anthracnose is an important disease of grapevines caused by the fungus Elsinoë ampelina. In recent years, there have been regular outbreaks in humid grape-growing regions around the world. Young leaves and berries are reported to be highly susceptible to E. ampelina, but detailed and seasonal development of age-related susceptibility remains unclear. Experiments were conducted under greenhouse and vineyard conditions by inoculating 1 to-19-day-old leaves, flowers and berries at different phenological stages of three grapevine cultivars (Vandal-Cliche, Marquette and Vidal). Leaf susceptibility was highest when inoculated at 1-2 days old, and inoculated leaves were moderately susceptible at 3-6 days old and almost resistant when older than 6 days. The influence of leaf age on anthracnose relative severity was adequately described by an exponential decay model. The susceptibility of the inflorescences was high when inoculated from their initiation to the full flowering (50% fall of the caps), and the inflorescences/flowers were moderately susceptible until veraison, after which the berries were practically resistant. The flower/berry susceptibility as a function of degree-days accumulated since April 1 was modeled using a sigmoid model. Based on this model, 50% disease incidence is reached when 656, 543 and 550 degree days are accumulated for the cultivars Vandal-Cliche, Marquette and Vidal, respectively. These results suggest that the risk of anthracnose development is high from bud-break to fruit set, and on newly-emerged leaves either early in the season or following pruning. More knowledge on anthracnose epidemiology is needed, but these results could be used to improve timing of fungicide applications and pruning activities.